Prediksi Pergerakan Bayangan Bumi Saat Terjadi Gerhana Bulan Menggunakan Ephemeris Hisab Rukyat - Muhammad Farid Azmi (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2018)
In this era, the prediction of lunar eclipse can be determined accurately with the astronomical data based algorithm. Usually, the prediction just compute the position and time of lunar eclipse without considered the movement of Earth shadow in the begginning to the end of eclipse. In this article the author explain how is the concept, algorithm, and analysis about the movement of Earth shadow on going lunar eclipse in certain local coordinate point, using the data from Ephemeris Hisab Rukyat.Keywords : Lunar Eclipse, Earth Shadow, Ephemeris Hisab Rukyat